Effective teacher? Student self-evaluation of development and progress on a teacher education programme. Issue 4 (3rd July 2016) - Gossman, Peter; Horder, Sue
Abstract : This article examines 28 teachers' views about their teacher education requirements. The participants were enrolled on a one-year full-time pre-service teacher education programme with a focus on post-compulsory education and training. The study examines how student teachers' self-evaluations against aspects of teaching professional practice changed, developed and evolved over the duration of the course. The results reveal a statistically significant improvement in self-evaluation when all areas of professional expertise are considered. In addition, the study reports a decline, as the programme progresses, in student-assessed need to learn about specific aspects of teaching.